Violence and the city in the modern Middle East - Fuccaro, Nelida (Stanford University Press, 2016)
Urban life and questions of violence / Nelida Fuccaro -- The semantics of violence and space / Rasmus Christian Elling -- Elite conflict and the urban environment : eighteenth-century Cairo / James E. Baldwin -- Urban space and prestige : when festivals turned violent in Jeddah, 1880s-1960s / Ulrike Freitag -- Citizenship rights and semantics of colonial power and resistance : Haifa, Jaffa, and Nablus, 1931-1933 / Lauren Banko -- Challenging the Ottoman pax urbana : intercommunal clashes in 1857 Tunis / Nora Lafi -- A tamed urban revolution : Saudi Arabia's oil conurbation and the 1967 riots / Claudia Ghrawi -- Making and unmaking spaces of security : Basra as battlefront, Basra insurgent, 1980-1991 / Dina Rizk Khoury -- A patriotic uprising : Baghdadi Jews and the Wathba / Orit Bashkin -- Dissecting moments of unrest : twentieth-century Kirkuk / Nelida Fuccaro -- War of clubs : struggle for space in Abadan and the 1946 oil strike / Rasmus Christian Elling -- Urban rupture : a fire, two hotels, and the transformation of Cairo / Yasser Elsheshtawy